High temperature mortality of Wolbachia impacts the sex ratio of the parasitoid Ooencyrtus mirus (Hymenoptera: Encyrtidae) - Power, Nancy R.; Rugman-Jones, Paul F.; Stouthamer, Richard; Ganjisaffar, Fatemeh; Perring, Thomas M. (PeerJ, 2022)
Background Wolbachia bacteria are estimated to occur in more than half of all insect species. In Hymenoptera, Wolbachia often manipulates its host’s reproduction to its own advantage. Wolbachia is likely the reason that males are rare in the uniparental Ooencyrtus mirus Triapitsyn & Power (Hymenoptera: Encyrtidae). The likelihood of producing male offspring can be increased by giving mothers a continuous supply of Bagrada hilaris (Burmeister) (Heteroptera: Pentatomidae) host eggs to parasitize for 2–3 weeks, by feeding the parents antibiotics, or by rearing parent wasps at high temperatures; all variables that have been shown to correlate with depleting Wolbachia titers in other organisms. The purpose of the current study was to determine whether thelytoky in O. mirus is due to Wolbachia, and if so, at what time in development the sex change occurs. We also wished to determine if Wolbachia removal results in the production of intersexes, as in some other hymenopterans. Finally, mating behavior was observed to see if and where it breaks down as a result of the species becoming thelytokous. Methods Females were collected from parental lines of O. mirus reared at 26, 30, 31, 32, 33, 34, and 36 °C. The offspring of these females were reared at 26 °C, and their sex-ratio was determined. In a subsequent experiment, the parental generation was switched between 26 °C and 36 °C during development to narrow down the critical period at which changes occurred that subsequently affected the sex-ratio of their offspring. Results The sex ratio was male biased in the offspring of O. mirus parents reared at 34 °C and 36 °C (high temperatures), even if the offspring themselves were reared at 26 °C. The constant temperature at which the percentage of males started to increase after two generations was 31 °C (10% males), rising to 39% males at 33 °C, and 100% males at 34 °C and 36 °C. Lasting more than 2 days, the critical period for the change toward a male biased sex ratio was during the second half of the parent’s development. Molecular diagnostic assays confirmed that O. mirus females contain Wolbachia and males do not. Examination of preserved males and male-female pairs under a dissecting microscope showed no signs of intersex characters. Observation of the mating behavior of live O. mirus showed that males initiate courtship by drumming their antennae on a female’s antennae, but after a few seconds, the females typically turn and walk away. However, a few instances of possible copulation were noted. Conclusions As hypothesized, the results indicated that thelytoky in O. mirus is likely mediated by Wolbachia bacteria. To maximize the population growth rate without generating males, the best temperature for mass rearing this species is 30 °C.
Keywords: Reproductive modification; Symbiosis; Bagrada hilaris; Biological control